The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/s20133713
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Kinematic Model of Shoulder Complex Based on Vicon Motion Capturing System: Generalized GH Joint with Floating Centre

Abstract: Due to the complex coupling motion of shoulder mechanism, only a small amount of quantitative information is available in the existing literature, although various kinematic models of the shoulder complex have been proposed. This study focused on the specific motion coupling relationship between glenohumeral (GH) joint center displacement variable quantity relative to the thorax coordinate system and humeral elevation angle to describe the shoulder complex. The mechanism model of shoulder complex was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition, stroke is becoming the leading cause of permanent disabilities worldwide, with over 15 million new cases each year and 50 million stroke survivors [ 3 ]; more than two-third of all patients affected by stroke have impaired upper limb motor function and have difficulty in independently performing ADLs [ 4 ]. Evidence has suggested that upper limb motor skills can be improved by following rehabilitation interventions [ 5 ], which attracts more and more scholars engaged in upper limb rehabilitation robot (ULRR) research [ 6 , 7 ], for the ULRRs have the potential to provide intensive rehabilitation consistently for a longer duration [ 8 ] irrespective of the skills and fatigue level of the therapist.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, stroke is becoming the leading cause of permanent disabilities worldwide, with over 15 million new cases each year and 50 million stroke survivors [ 3 ]; more than two-third of all patients affected by stroke have impaired upper limb motor function and have difficulty in independently performing ADLs [ 4 ]. Evidence has suggested that upper limb motor skills can be improved by following rehabilitation interventions [ 5 ], which attracts more and more scholars engaged in upper limb rehabilitation robot (ULRR) research [ 6 , 7 ], for the ULRRs have the potential to provide intensive rehabilitation consistently for a longer duration [ 8 ] irrespective of the skills and fatigue level of the therapist.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of ULRRs that have been studied the most, the exoskeleton type and end-effector type [ 9 ]. For the exoskeleton-based ULRR, the robots can resemble human limbs as they are connected to patients at multiple points and their joint axes match with human joint axes; training of specific muscles by controlling joint movements at calculated torques is possible, and the number of anatomical movements can exceed six; typical exoskeleton ULRRs are SUEFUL-7 [ 10 ], CADEN-7 [ 11 ], ARMin III [ 12 ], L-EXOS [ 13 ], ExoRob [ 14 ], RUPERT [ 15 , 16 ], BONES [ 17 ], ULEL [ 18 ], and Limpact [ 19 ]; nonetheless, increasing the number of movement parts increases the number of device modules, so the system setup becomes difficult; moreover, since the shoulder has a variable joint center, the mechanical design and control algorithms become more complicated [ 7 ]. By comparison, the end-effector type ULRRs are connected to patients at one distal point, and their joints do not match with human joints; force generated at the distal interface changes the positions of other joints simultaneously, making isolated movement of a single joint difficult [ 20 , 21 ]; the advantages of the end-effector type ULRRs are that they have a simple structure and less complex control algorithms and can avoid abnormal motion and posture of the target anatomical joints and specific muscles; typical end-effector type ULRRs are MIT-Manus [ 22 ], AMES [ 23 ], iPAM [ 24 ], PASCAL [ 25 ], Fourier M2 [ 26 ], EEULRebot [ 27 ], hCAAR [ 28 ], PARM [ 29 ], CASIA-ARM [ 30 ], Sophia-3 [ 31 ], and BULReD [ 2 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an in-depth analysis of shoulder movement is essential for understanding the mechanism of SR robots. Various studies on the mechanism of shoulder movement have been conducted [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the shoulder elevation and depression phases, and the movement coupling relationship between the displacement of the glenohumeral (GH) joint center with respect to the thoracic coordinate system and elevation of the humerus was investigated. As a result, a new design model for an upper extremity rehabilitation robot consistent with the actual situation of the human body structure was developed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%